A titanium screw-retaining temporary denture on the raw surface muscular flap for the immediate maxillary reconstruction. Issue 1 (January 2016) - Miyashita, Hidetaka; Asoda, Seiji; Horie, Nobuyuki; Usuda, Shin; Kato, Shin; Muraoka, Wataru; Yamada, Yuka; Yoshikawa, Momoko; Hasegawa, Toshihiro; Onizawa, Katsuhiro; Tanaka, Ichiro; Yazawa, Masaki; et al.
Abstract: Objective: In any immediate reconstruction of the maxillofacial defect after total maxillectomy, the defect is often covered with a flap, however, dentures cannot be maintained stably by the flap, because of the high mobility and large amount of displacement of the flap under pressure. Therefore, we developed a method in which a muscle flap is transplanted without creating a skin island in the oral cavity and a denture is immediately fixed with titanium screws, and obtained favorable results. Patients and methods: The subjects were 9 patients who underwent resection for maxillary sinus cancer. In all patients, a free rectus abdominis muscle flap was used for the reconstruction and the raw surface of the muscle tissue was left in the oral cavity without creating a skin island. Dentures that had been made preoperatively were fixed on the remaining palate and alveolus with titanium screws for one month, so that they covered the muscle tissue. Results: Good palatal morphology was formed without hanging down after epithelialization of the surface of the muscle tissue. In comparison with the preoperative levels, the masticatory and conversational functions recovered to 77% and 90%, on average. Conclusions: Our method is considered to be one of the useful reconstruction methods for maxillofacial defects.